Deprivation and mass screening: Survival of women diagnosed with breast cancer in France from 2008 to 2010. (June 2019) - Poiseuil, Marie; Coureau, Gaëlle; Payet, Catherine; Savès, Marianne; Debled, Marc; Mathoulin-Pelissier, Simone; Amadeo, Brice
Highlights: Women with breast cancer participating to mass screening had higher survival. Attender women to mass screening had a good survival regardless deprivation. Survival was lower for non-attender women in deprived areas. Effect of mass screening in survival seemed higher for women in deprived areas. Abstract: Background: Some studies have investigated the role of socio-demographic inequalities in the association between screening and survival. However, in France, no study has been conducted to describe the socio-demographic characteristics and survival of women with breast cancer based on their participation to mass screening. The aim of this study was to assess the impact of socio-demographic inequalities on the association between participation in mass screening program and survival of women with breast cancer. Methods: Data for 2, 244 women aged 50–74 years diagnosed with breast cancer over the period 2008–2010 were obtained from the cancer registry and the screening structure of Gironde. We used the aggregated European Deprivation Index (EDI) to define the deprivation level of women. Net survival rates were estimated with the Pohar-Perme method, with and without correcting for lead-time bias. Results: Survival rates were lower for non-attenders than for screen-detected women (83.8% vs 97.3%, p < 0.0001), even after correcting for lead-time bias. Among the most deprived women, the survival rate was significantly different between non-attenders and screen-detected women (78.1% vs 95.6%, p = 0.0002), suggesting an important effect of mass screening in this group. Conclusion: The introduction of incentive actions in deprived areas could play a key role in the adherence of women to mass screening and in improving their survival in case of a breast cancer diagnosis.